A novel cryptosystem based on Gluškov product of automata - Dömösi, Pál; Horváth, Géza (Acta Cybernetica, 2015)
The concept of Gluškov product was introduced by V. M. Gluškov in 1961. It was intensively studied by several scientists (first of all, by Ferenc Gécseg and the automata-theory school centred around him in Szeged, Hungary) since the middle of 60’s. In spite of the large number of excellent publications, no application of Gluškov-type products of automata in cryptography has arisen so far. This paper is the first attempt in this direction.